Testing For Unit Roots In The Presence Of Multiple Trend Breaks: An Application To Chilean Inflation Rate Series - El-Ramly, Hala M. (The international business & economics research journal, 2011)
This paper is an application of the subject of testing for unit roots in a time series in the presence of structural change. The series used is that of the Chilean monthly inflation rate. A characteristic of this series is that, with the exception of the 1972-1977 period during which the inflation rate in Chile greatly accelerated then decelerated, the Chilean inflation rate over the 40-year period of the study stayed within a limited range. In spite of this relatively stable performance, the application of the standard unit root tests to the series results in the inability to reject the unit root. However, when a test that allows for three endogenously determined breaks in the slope of the trend function of the series is used to account for the structural change of the 1972-1977 episode; the result is a strong rejection of the unit root in favor of a, more reasonable, stationary characterization of the series.